The Role of Cognitive Control in Language Comprehension: Commentary on Kuz et al. (2024) - Jared M. Novick; Susan Teubner-Rhodes; Albert E. Kim (Languages)
This commentary examines a recent study that challenges the view that cognitive control supports the resolution of linguistic ambiguities. We critique the study’s methodological limitations, particularly its reliance on self-paced reading, which lacks the sensitivity to detect the effects of cognitive control on language processing. Furthermore, we address theoretical issues with the proposal that visual attention, rather than cognitive control, explains prior findings from the visual-world paradigm. By highlighting the linking assumptions behind the visual-world paradigm, we argue that eye movement patterns reflect syntactic parsing decisions and cannot be explained by visual attention alone. Considering these factors and the broader body of evidence, we maintain that cognitive control remains a key mechanism in language comprehension, despite the alternative account presented in the target study.